2017
DOI: 10.1111/ene.13303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pramipexole extended‐release in Parkinson's disease: a review based on meta‐analysis of randomized controlled trials

Abstract: Pramipexole ER is as safe and effective as pramipexole IR in the treatment of Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Meanwhile, pramipexole caused muscle weakness, peripheral edema, and back pain. The study results were parallel with the results of a double-blinded study (11). Unlike PP cohort, in SG cohort, patients with dyskinesias were reported.…”
Section: Adverse Effects and Hospitalizationsupporting
confidence: 73%
See 1 more Smart Citation
“…Meanwhile, pramipexole caused muscle weakness, peripheral edema, and back pain. The study results were parallel with the results of a double-blinded study (11). Unlike PP cohort, in SG cohort, patients with dyskinesias were reported.…”
Section: Adverse Effects and Hospitalizationsupporting
confidence: 73%
“…After 3-years of treatment, in the same manner, motor and daily living tasks (UPDRS III scale) of the patients of PP cohort were also improved. The study results were parallel with the results of double-blind studies (11,12). Pramipexole may also delay the progression of disease in patients with confirmed Parkinson's disease.…”
Section: Expendituresupporting
confidence: 65%
“…Nausea was the only side‐effect with a higher prevalence in pramipexole than placebo and SSRIs. Unexpectedly, studies on individuals treated with pramipexole for depression did not report some side‐effects commonly reported in studies on individuals treated with pramipexole for Parkinson's disease, such as lethargy, gambling, hypersexuality and compulsive shopping . In our opinion, this difference might be due to the different neurobiological dysfunctions underlying depression and Parkinson's disease or to the relatively small number of patients with depression treated with pramipexole, not sufficient to detect infrequent adverse events.…”
Section: Discussionmentioning
confidence: 61%
“…The IR formulation was first approved for use in the USA in 1997 [6], and then received European Medicines Agency approval in 1998 [7]. The ER formulation was subsequently developed and was shown to be associated with better adherence to the drug regimen, more constant blood level, and favorable clinical response and safety profiles in clinical trials [8][9][10][11]. Investigators from Italy studied Parkinson's disease patients from a single center in Rome and reported that the use of ER dopamine agonists, including transdermal rotigotine and ER formulations of oral ropinirole and pramipexole, was associated with lower daily levodopa doses and decreased frequency of adverse effects [12].…”
Section: Introductionmentioning
confidence: 99%